Production of some coagulant materials from galvanizing workshop waste - Cici, M; Cuci, Y (Pergamon-Elsevier Science Ltd, 1998)
The aim of this study was to investigate production of some coagulant reagents which have been widely used in all water coagulation treatments using galvanizing waste of the Karadeniz Iron-Steel Plant in Turkey. The waste sample was analyzed by atomic absorption spectrophotometry and a gravimetric procedure. With different techniques, ferric chloro sulphate, FeClSO4, ferric sulphate, Fe-2(SO4)(3), sodium ferrate, Na2FeO4 and potassium ferrate, K2FeO4 were obtained from galvanizing waste under laboratory conditions. Then the composition of each reagent was identified by qualitative and quantitative analyses, separately. (C) 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Recovery; Copper